The catechol‐O‐methyltransferase (COMT) Val158Met genotype modulates working memory‐related dorsolateral prefrontal response and performance in bipolar disorder. (23rd May 2017) - Miskowiak, KW; Kjærstad, HL; Støttrup, MM; Svendsen, AM; Demant, KM; Hoeffding, LK; Werge, TM; Burdick, KE; Domschke, K; Carvalho, AF; Vieta, E; Vinberg, M; et al.
Abstract : Objectives: Cognitive dysfunction affects a substantial proportion of patients with bipolar disorder (BD), and genetic‐imaging paradigms may aid in the elucidation of mechanisms implicated in this symptomatic domain. The Val allele of the functional Val158Met polymorphism of the catechol‐O‐methyltransferase ( COMT ) gene is associated with reduced prefrontal cortex dopamine and exaggerated working memory‐related prefrontal activity. This functional magnetic resonance imaging (fMRI) study investigated for the first time whether the COMT Val158Met genotype modulates prefrontal activity during spatial working memory in BD. Methods: Sixty‐four outpatients with BD in full or partial remission were stratified according to COMT Val158Met genotype (ValVal [n=13], ValMet [n=34], and MetMet [n=17]). The patients completed a spatial n‐back working memory task during fMRI and the Cambridge Neuropsychological Test Automated Battery (CANTAB) Spatial Working Memory test outside the scanner. Results: During high working memory load (2‐back vs 1‐back), Val homozygotes displayed decreased activity relative to ValMet individuals, with Met homozygotes displaying intermediate levels of activity in the right dorsolateral prefrontal cortex (dlPFC) ( P =.016). Exploratory whole‐brain analysis revealed a bilateral decrease in working memory‐related dlPFC activity in the ValVal group vs the ValMet group which was not associated with differences in working memory performance during fMRI. Outside the MRI scanner, Val carriers performed worse in the CANTAB Spatial Working Memory task than Met homozygotes ( P ≤.006), with deficits being most pronounced in Val homozygotes. Conclusions: The association between Val allelic load, dlPFC activity and WM impairment points to a putative role of aberrant PFC dopamine tonus in the cognitive impairments in BD.